A CRÍTICA DIANTE DO TRABALHO IMATERIAL DA MULTIDÃO - Luciano Barbosa Justino (Revista Brasileira de Literatura Comparada, 2017)
My objective, in this paper, is to make a double move: to show how the multitude’s perspective is fundamental in order to understand what I consider to be one of the basis of Brazilian Contemporary Literature, the meet up with the otherness; to analyze how such Literature require from us new methods for researching and approaching the literary pieces. To do so, I intend to render problematic on the literary critique’s identity presumptions as my heuristic principle to enter and exit the pieces, and from the concept of immaterial work, to show how the meet up with the otherness, in the contemporary literature, implies to consider the unavoidable productivity of secondary characters, those that make the immaterial work with the language into ways of resistance and singularization potential.